Silver Diamine Fluoride: Game Changer in Dental Public Health: A Review - Sharmistha Mohanty1 , Dharmashree Satyarup2 , Ramesh Nagarajappa3 , Ipshita Mahapatra1 , Radha Prasa (Indian Journal of Forensic Medicine & Toxicology, 2020)
A major part of the world population is affected with carious teeth, among which the number of childrenaffected is maximum. Carious lesions are more common in susceptible, uninsured and financially weakpopulations. Caries which are not treated for a very long period along with no utilization of available servicesin both developing and underdeveloped countries pose an essential public health question. Children havelimited adaptive capacity which may also lead to difficulty in some treatment procedures. Hence, the needfor an efficient and affordable approach for dental caries treatment was required in areas that have a finiteaccess to oral health care services like the school children. Nowadays, Silver Diamine Fluoride (SDF) isvery much in demand as it can control caries progression and is very less technique sensitive. This approachdoes not require caries excavation using instruments, in addition silver has many antimicrobial propertiesand fluoride helps in remineralization.